In Situ Study of the Electrochemical Migration of Tin under Bipolar Square Wave Voltage. Issue 6 (1st January 2017) - Zhong, Xiankang; Chen, Longjun; Hu, Junying; Shi, Yufan; Zhang, Zhi; Zeng, Dezhi; Shi, Taihe
Abstract : The electrochemical migration (ECM) of tin under bipolar square wave voltage with various time periods was in situ studied using optical and electrochemical techniques. The results show that there is no dendrite growth but only precipitate formation for the time periods from 1 to 100 s during the same test time interval. The amount of precipitates increases with the increasing time period from 1 to 100 s. Moreover, the locations where the precipitates appear are time period dependent. As the time period increases to 200 s, both dendrite growth and precipitates formation can be observed during the ECM test and the short circuit occurs at the end of the third semi-cycle. From one semi-cycle to the next semi-cycle, the switch between the voltage and its reverse voltage derived from the bipolar square wave during the ECM of tin results in a periodic switch between cathodic polarization and anodic polarization applied on the same electrode, periodic changes in the migration direction of ions and a circulation between dendrite growth and its re-dissolution. Therefore, it is believed that the ECM processes including ion formation, ion migration, precipitate formation and dendrite growth under bipolar square wave voltage are strongly dependent upon the semi-cycle.